NetIQ delves deeper into Unix, Linux territories - Jennifer Hagendorf Follett (CRN, 2002)
NetIQ Tuesday plans to expand its offering in the Unix and Linux infrastructure management space with the launch of several new modules for its AppManager product suite. The company is moving deeper into Unix/Linux environments with support for Web infrastructure, including Web servers, applications servers and back-end databases.